Pertanggungjawaban Korporasi Terhadap Kandungan Non-Halal Pada Produk Makanan Sebagai Upaya Perlindungan Konsumen - Asiyah Jamilah; Hari Sutra Disemadi; Nyoman Serikat Putra Jaya (Faculty of Law, Andalas University, 2020)
The development of the corporate function as a means of organizing socially oriented societies towards profit-seeking activities not least triggers negative impacts. One of the negative impacts is the emergence of criminal acts committed by corporations. In order to get as much profit as possible, corporations take actions that can cause losses to consumers, one of which is by mixing non-halal content into products labeled as halal. The purpose of this article are, First, to provide an overview of corporate legal policy as a criminal law subject and Second, to be able to know the corporate responsibility for non-halal content in halal-certified food products as an effort to protect consumers. The results of this study are policies regarding corporations as subjects of criminal law in which their actions can be prosecuted and held criminal liability are contained in special legislation outside the criminal code. Corporate liability regarding non-halal content in halal-certified food products follows a direct accountability system. This means that criminal liability for violations of the halal label can be addressed either to individuals or corporations where corporate responsibility is imposed on its management as stipulated in Article 61 of The Consumer Protection Laws